Creative Economy Empowerment with Technopreneur Training for Muhammadiyah Teachers in Tasikmalaya City - Muhammad Taufiq; Maesaroh Lubis; Hani Rubiani (AbdimasMu UMTAS, 2022)
Community service as a measure to socialize the Creative Economy through Technopreneur Training involves Muhammadiyah teachers from elementary to middle and high levels in Muhammaduyah Regional Leadership Tasikmalaya City is intended that teachers can operate businesses in their free time as teachers about business online by utilizing HP or Laptop/PC technology devices. Makning products for training participants can be as producers in the form of culinary, merchandise, resellers or as affiliates of goods or services that are created in such a way as a top products. The implementation of this training event was held on November 20, 2021 in the Auditorium of the University of Muhammadiyah Tasikmalaya. Community Service Activities had done well, this can be measured from the level of participation of participants during the training who had high enthusiasm and responsibility. This activity is expected to motivate Muhammadiyah teachers in order to improve the community's economy in their respective places or regions.